تطبيق القيم القرآنية المتعلقة بصلة الإنسان بربه لدى معلمي التربية الإسلامية على طلابهم في المرحلة الثانوية في دولة الكويت: The application of Quranic values by Teachers of Islamic Education to Their Students at the Secondary Stage in the State of Kuwait - Alanazi, Ahmed; Mohamed Adnan, Mohamad Azrien (Al-Basirah Journal, 2024)
This study aimed to reveal the extent to which Islamic education teachers apply the Qur’anic values ​​to their students at the secondary stage in the State of Kuwait. The researchers used the descriptive survey method. The study sample consisted of (82) individuals. The most important results of the study was that secondary school teachers apply the Qur’anic values ​​in general education schools and in private (bilingual) schools in the State of Kuwait in a large extent. The results also revealed that there were no statistically significant differences between the average responses of the sample members to the type of schools, or the educational department, while there were statistically significant differences between the average responses of the sample members attributable to job experience in favor of higher job experience.